Syntactic and Semantic Comparison of Transitive and Intransitive Verbs in Arabic Sentences: A Linguistic Approach - AoumeurSoufghalem; Muhammad Qadhaf (IJAS: International Journal of Arabic Studies, 2024)
This study explores the syntactic and semantic differences between transitive (muta'addi) and intransitive (lazim) verbs in Arabic sentences. The primary aim is to analyze how these two verb types affect sentence structure and meaning in the Arabic language. Transitive verbs require a direct object to complete their meaning, which impacts sentence complexity and the relationship between subject and object. In contrast, intransitive verbs do not require an object, leading to simpler sentence structures. The research focuses on the syntactic analysis of sentence construction involving transitive and intransitive verbs, highlighting how the presence or absence of an object influences the positioning of sentence elements. From a semantic perspective, transitive verbs convey more specific and detailed meanings due to their direct interaction with objects, while intransitive verbs provide more general and straightforward meanings. This study utilizes classical and modern Arabic texts to collect and analyze examples of both verb types, demonstrating their influence on the overall meaning of the sentences in which they are used. The findings emphasize the importance of understanding these differences for learners and educators of Arabic, as they play a crucial role in sentence formation and meaning interpretation. The study contributes to a deeper understanding of Arabic grammar, particularly in the context of language teaching and linguistic analysis.